2017
DOI: 10.1016/j.jcis.2017.03.078
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photocatalytic degradation of dyes over graphene/Pd/TiO2 nanocomposites: TiO2 nanowires versus TiO2 nanoparticles

Abstract: In this study, at first, TiO nanowire was prepared by an alkaline hydrothermal process. In the following, Gr/Pd/TiO-NPs and Gr/Pd/TiO-NWs were synthesized by a combination of hydrothermal and photodeposition methods. The properties of as prepared products were characterized using XRD, FT-IR, SEM, DRS, TEM, ICP-OES, EDS and TGA analysis. SEM results confirmed nanodimension structure for all samples. Also the band gap values obtained using DRS technique suggests that all the samples have semiconductor behavior. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(76 citation statements)
references
References 40 publications
2
71
0
Order By: Relevance
“…Different techniques are used to remove amido black from water. These include adsorption, electrochemical process, photodegradation, ultrafiltration, reverse osmosis, coagulation and biochemical process (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). It is observed that these methods have certain limitations like not fast, which cannot be used at a large scale.…”
Section: Introductionmentioning
confidence: 99%
“…Different techniques are used to remove amido black from water. These include adsorption, electrochemical process, photodegradation, ultrafiltration, reverse osmosis, coagulation and biochemical process (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). It is observed that these methods have certain limitations like not fast, which cannot be used at a large scale.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37][38][39] Another possible application of these materials is the photocatalytic reduction of CO 2 to methane. [35][36][37][38][39] Another possible application of these materials is the photocatalytic reduction of CO 2 to methane.…”
Section: Titaniumd Ioxide/graphene/carbon Nanotubes Nanostructuresmentioning
confidence: 99%
“…Ataee‐Esfahani et al have used gold–platinum nanoparticles as an electrocatalyst for methanol oxidation . Masoud Salavati‐Niasari and his coworkers used neodymium vanadate, silver/titania, praseodymium oxide, copper indium sulfide, zirconia, and zinc titania nanoparticles and cupper iron oxide/carbon nanotube/graphene, dysprosium tin oxide/tin oxide, cadmium sulfide/carbon, and palladium/titania/ graphene nanocomposites as photocatalysts for the degradation of various water pollutants. They have proved, through band gap calculations, that bimetallic nanoparticles are good photocatalysts .…”
Section: Introductionmentioning
confidence: 99%